Antimicrobial activities of some narrow endemic gypsopyhte - Ocak, Esma; İnci, Şule; Öztürk, Derviş; Şafak, Sanem Akdeniz; Özdeniz, Ebru; Kırbağ, Sevda; Kurt, Latif (İstanbul Üniversitesi, 2021)
Background and Aims: In this study, antimicrobial activities of extracts obtained from narrowly dispersed local endemic gypsophytes grown in extreme habitats were investigated for the first time. The aim of this study was to analyzed antimicrobial effects of narrow endemic plants that are Thymus ekimii Yildirimli, Verbascum gypsicola Vural & Aydogdu, Glaucium secmenii Yildirimli and Psephellus erzincani Wagenitz & Kandemir. Methods: Antimicrobial activity of T. ekimii, V. gypsicola, G. secmenii and P. erzincani were determined according to the disk diffusion method. The microorganisms used for the present investigation; gram positive bacteria, gram negative bacteria and yeasts (Bacillus megaterium DSM32, Escherichia coli ATCC25922, Candida albicans FMC17). Results: According to the results obtained, P. erzincani showed the best antimicrobial activity against B. megaterium DSM32 (23 mm), E. coli ATCC25922 (15 mm) and C. albicans FMC17 (23mm), respectively. Conclusion: This study showed that extracts of these endemic plants have the potential for use as antimicrobial agents, especially P. erzincani.
Keywords: Pharmacology and Pharmaceutical Sciences; Eczacılık ve İlaç Bilimleri; Health Care Administration; Sağlık Kurumları Yönetimi